Collaboration of Implementation of PBL and PjBL in Increasing Students' Critical Awareness of the Social Impact of ICT at SMP Negeri 2 Jereweh - Milosopa, Erna (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Although today's students are proficient in the use of information and communication technology (ICT), their critical awareness of the negative social impact of ICT is still low. This study aims to apply the Problem Based Learning (PBL) and Project Based Learning (PjBL) learning model in increasing students' critical awareness of digital social issues such as the spread of hoaxes, cyberbullying, access inequality, and digital ethics. Using a descriptive qualitative approach, data was collected through observation, interviews, and documentation of seventh grade students at SMP Negeri 2 Jereweh, with a total of 24 people. The learning implementation was conducted in three stages with a project approach and real problem solving related to social issues in technology. The implementation results showed an increase in concept understanding, active involvement of students in discussions, and the ability to convey creative solutions to the problems raised. The results showed that the application of PjBL was able to encourage students to think critically, conduct social analysis, and produce reflective products related to ICT issues such as personal data security, digital dependence, and social media ethics. In conclusion, the PjBL model is effective in shaping students' critical understanding of social reality influenced by ICT development.